Effect of an Orally Active Th2 Cytokine Inhibitor, Suplatast Tosilate, on “Atopic Cough” - Ishiura, Yoshihisa; Fujimura, Masaki; Yamamoto, Hiroki; Nobata, Kouichi; Ishiguro, Takashi; Ogawa, Haruhiko; Myou, Shigeharu (Arzneimittelforschung, 2008)
– “Atopic cough” is a new clinical entity that presents with isolated chronic bronchodilator-resistant cough accepted in the Japanese Respiratory Society Guidelines for Management of Cough. The essential features are eosinophilic tracheobronchitis, increased cough reflex sensitivity and an atopic constitution. It has been suggested that activated helper Tlymphocytes and the cytokines which are produced by these cells are involved in the pathogenesis, but the relationship between helper T cell-derived cytokines and the airway cough reflex sensitivity remains unknown.– The effect of an orally active Th2 cytokine inhibitor, suplatast tosilate (CAS 94055-76-2, IPD™; 300 mg/day), on the cough response to inhaled capsaicin (CAS 404-86-4) was examined in ten patients with atopic cough. The capsaicin cough threshold, defined as the lowest concentration of capsaicin eliciting five or more coughs, was measured as an index of airway cough reflex sensitivity. The serum total immunoglobulin E (IgE) level and the peripheral blood eosinophil count were also determined after treatment with suplatast tosilate.– The cough threshold measured after four weeks of treatment with suplatast tosilate was significantly increased compared to the value obtained with placebo, along with a decrease of the serum IgE level and peripheral eosinophil count.– Th2 cytokines may increase the airway cough reflex sensitivity in patients with atopic cough. Oral administration of suplatast tosilate may be a novel therapy for atopic cough.
Keywords: Antiallergic agents; CAS 94055-76-2; Eosinophilic tracheobronchitis,; IPD™; Suplatast tosilate, clinical study, effect on cough reflex sensitivity; Th2 cytokines